Pembagian Masker dan Hand Sanitizer dalam Upaya Pencegahan Penularan COVID-19 Era New Normal Pada Mahasiswa di Lingkungan Kampus - Siti Nur Asyah Jamillah Ahmad Nur (LPPM Stikosa - AWS, 2022)
Community discipline in carrying out Health protocols is very important in preventing the transmission of COVID-19. Educational institutions are one of the potential places for the transmission of COVID-19. With the new normal era, student activities in the campus environment are increasing so that the application of health protocols is maintained, including the use of masks in the campus environment. Everyone's awareness is a challenge in an effort to break the chain of transmission of COVID-19. The purpose of community service is to help prevent the spread of COVID-19 in the campus environment. The method of service carried out is the distribution of masks and hand sanitizers as well as education about preventing COVID-19 to students in the campus environment. Community service activities distributing masks and hand sanitizers can run well. The students gladly accepted and were grateful for the masks and Hand Sanitizer that had been distributed.